Strengthening the food systems governance evidence base: Supporting commensurability of research through a systematic review of methods - Delaney, A.; Evans, T.; McGreevy J; Blekking, Jordan; Schlachter, Tyler; Korhonen-Kurki, Kaisa; Tamás, Peter A.; Crane, Todd A.; Eakin, H.; Förch, Wiebke; Jones, L.; Nelson, D.R.; et al. (2016)
Governance of food systems is a poorly understood determinant of food security. Much scholarship on food systems governance is non-empirical, while existing research is often case study-based and theoretically and methodologically incommensurable. This frustrates aggregation of evidence and generalisation. We undertook a systematic review of methods used in food systems governance research with a view to identifying a core set of indicators for future research. We gathered literature through a structured consultation and sampling from recent reviews. Indicators were identified and classified according to the levels and sectors they investigate. We found a concentration of indicators in food production at local to national levels and a sparseness in distribution and consumption. Unsurprisingly, many indicators of institutional structure were found, while agency-related indicators are moderately represented. We call for piloting and validation of these indicators and for methodological development to fill gaps identified. These efforts are expected to support a more consolidated future evidence base and eventual meta-analysis.